PET/CT for Inflammatory Diseases 2019
DOI: 10.1007/978-981-15-0810-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Basic Science of PET Imaging for Inflammatory Diseases

Abstract: FDG-PET/CT has recently emerged as a useful tool for the evaluation of inflammatory diseases too, in addition to that of malignant diseases. The imaging is based on active glucose utilization by inflammatory tissue. Autoradiography studies have demonstrated high FDG uptake in macrophages, granulocytes, fibroblasts, and granulation tissue. Especially, activated macrophages are responsible for the elevated FDG uptake in some types of inflammation. According to one study, after activation by lipopolysaccharide of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 178 publications
(234 reference statements)
0
4
0
Order By: Relevance
“…FDG-PET/CT has utility in the staging, restaging, and assessment of therapeutic effects in malignancy, and is used in the management of patients with malignancy (17). Because FDG accumulates in activated inflammatory cells including neutrophils and macrophages, FDG-PET/ CT has huge potential for diagnosing and monitoring inflammatory disease (18).…”
Section: Fdg-pet/ctmentioning
confidence: 99%
See 1 more Smart Citation
“…FDG-PET/CT has utility in the staging, restaging, and assessment of therapeutic effects in malignancy, and is used in the management of patients with malignancy (17). Because FDG accumulates in activated inflammatory cells including neutrophils and macrophages, FDG-PET/ CT has huge potential for diagnosing and monitoring inflammatory disease (18).…”
Section: Fdg-pet/ctmentioning
confidence: 99%
“…However, various diseases can mimic these features, including other viral pneumonias (7), and chest CT is therefore not currently recommended as an initial screening tool (8). Following numerous reports regarding the CT appearance of COVID-19, several groups have reported [ 18 F]-2-fluoro-2-deoxy-D-glucose (FDG)positron emission tomography/computed tomography (PET/CT) imaging findings of COVID-19 (9)(10)(11)(12)(13)(14)(15)(16). We experienced two measurements of FDG-PET/CT in a COVID-19 infected patient, one was 4 weeks from symptoms onset and the other was 4 weeks after the first FDG-PET/CT scan (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…The distinct spatiotemporal patterns in cytokine production between intradermal and intranasal infection implicate potential differences in the propensity to increase glycolysis after FTT infection. Measuring distribution and uptake of glucose derivatives with preclinical imaging techniques can identify tissues where increased glycolysis is actively supporting inflammatory functions [ 19 , 20 ]. Therefore, we next assessed the tissue distribution of the glucose derivative XenoLight RediJect 2-DG 750 (RJ2-DG-750) using optical fluorescence imaging in mice following i.n.…”
Section: Resultsmentioning
confidence: 99%
“…Several articles have earlier summarized reported candidate CSF1R PET tracers, but only briefly. , A growing number of candidate PET tracers for imaging brain CSF1R are now being reported (Table ). In this Review, we discuss and compare the performances of all candidate CSF1R PET tracers reported to date and their issues.…”
mentioning
confidence: 99%